KERAGAMAN GENETIK POPULASI E. oleifera DAN POPULASI E. guineensis x E. oleifera PADA KOLEKSI PLASMA NUTFAH PPKS - Rokhana Faizah; Sri Wening; Hernawan Yuli Rahmadi; Abdul Razak Purba (Jurnal Penelitian Kelapa Sawit, 2016)
The oil palm species of Elaeis oleifera have some superior characters not possessed by E. guineensis species. The cross between E. oleifera x E. guineensis (E. o x E. g.) Is carried out to insert the superior character of E. oleifera into the E. guineensis species and to obtain individuals who possess a superior characteristic blend of both species. This study aims to determine the genetic diversity within and between populations of E. oleifera, as well as relationships between E. oleifera, E. guineensis and its interspecific hybrids. A total of 8 germplasm populations used were E. oleifera originating from Suriname and Brazil, E. guineensis population of Dura Deli and SP540T, and interspecific crosses of hybrid E. guineensis x E. oleifera from Colombia, hybrid E. guineensis x E. oleifera which is presumably from Colombia, as well as hybrid E. guineensis x E. oleifera from Brazil. A total of sixteen Simple Sequence Repeat (SSR) markers were used to analyze 92 individuals from 8 populations. PCoA results show that 8 Elaeis populations cluster in each group. The hybrid population of E. guineensis x E. oleifera suspected of Colombia has a very close kinship relationship with hybrid E. guineensis x E. oleifera from Colombia and clumped in the same quadrant. This suggests that the hybrid is indeed a hybrid of E. guineensis x E. oleifera from Colombia. The population of E. oleifera from Suriname showed the lowest genetic diversity, with the number of different alleles, specific alleles, heterozygosity values, and the percentages of polymorphic loci sequentially were 1.37, 0.18, 0.09, and 37.50%. While the population of interspecific interspecific crossbreeds of the E. oleifera species showed the highest genetic diversity with values ​​of 3.81, 0.43, 0.62 and 100%.